Aerobic and anaerobic swimming force evaluation in one single test session for young swimmers - de Barros Sousa, F. A.; Almeida Rodrigues, N.; Dalcheco Messias, L. H.; Borges Queiroz, J.; Barros Manchado-Gobatto, F.; Gobatto, C. A. (International Journal of Sports Medicine, 2017)
This study aims to propose and validate the tethered swimming lactate minimum test (TSLacmin) estimating aerobic and anaerobic capacity in one single test session, using force as measurement parameter. 6 male and 6 female young swimmers (age=15.7±1.1 years; height=173.3±9.5 cm; weight=66.1±9.5 kg) performed 4 sessions comprising i) an all-out 30 s test and incremental test (TSLacmin); ii) 30 min of tethered swimming at constant intensity (2 sessions); iii) free-swimming time trials used to calculate critical velocity. Tethered swimming sessions used an acquisition system enabling maximum (Fmax) and mean (Fmean) force measurement and intensity variation. The tethered all-out test lasting 30 s resulted in hyperlactatemia of 7.9±2.0 mmol·l-1. TSLacmin presented a 100% success applicability rate, which is equivalent to aerobic capacity in 75% of cases. TSLacmin intensity was 37.7±7.3 N, while maximum force in the all-out test was 105±27 N. Aerobic and anaerobic TSLacmin parameters were significantly related to free-swimming performance (r=-0.67 for 100 m and r=-0.80 for 200 m) and critical velocity (r=0.80). TSLacmin estimates aerobic capacity in most cases, and both aerobic and anaerobic force parameters are well related to critical velocity and free swimming performance.